The Effect Of Financial Literacy, Perceived Usefulness, And Ease Of Use Of Electronic Wallet On Impulsive Buying Behavior Of College Students - Putri Febrianti Azzahra; Rona Tumiur Mauli C. Simorangkir (Proceeding International Annual Conference Economics, Management, Business, and Accounting, 2023)
This study aims to analyze the effect of financial literacy, perceived usefulness, and perceived ease of use of e-wallets on impulsive buying behavior of Mercu Buana University students. This type of research is quantitative research, with data collection methods using questionnaires via the Google Form link and distributed digitally to respondents. Theory Planned of Behavior (TPB) and Technology Acceptance Model (TAM) are used in this study. The population in this study was 1138 people. The sample selection method used was simple random sampling with a sample size of 296, and 307 respondents were found in this study. The object of this research is e-wallet user for students who are currently pursuing undergraduate education at Universitas Mercu Buana Meruya, Faculty of Economics and Business, majoring in accounting, class of 2018-2021. The data analysis method used is the Partial Least Square Structural Equation Modeling (PLS- SEM) analysis technique using the SmartPLS version 3 software analysis tool. What differentiates this research from previous research is the object of research and the time this research was conducted, where the object of this research is Mercu Buana Meruya University students majoring in accounting class 2018-2021. Based on the results of the financial literacy, and perceived ease of use have a significant positive effect, while perceived usefulness has no effect on impulsive buying behavior. The limitations of this study are that the scope is not too broad, where researchers only focus on one location. And for further research it is better to add other variables that are outside this research.